DEVELOPMENT OF A CHEMISTRY E-MODULE BASED ON EXPERIENTIAL LEARNING ON REACTION-RATE MATERI - Alfina Alfina; Dewi Syafriani (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This research aims to develop chemistry e-modules based on Experiential Learning (EL) model on reaction rate material and test its validity, practicality, and effectiveness. The method used is the ADDIE development model. The research subjects were 30 students of class XI MIPA 2 at SMA Swasta PAB 8 Saentis. The results of the validity of the e-module by material and media experts showed a percentage of content feasibility of 83%, presentation of 84%, EL aspects of 80%, graphics of 81%, and language of 87%, with an average of 83% which is included in the â€œvery feasibleâ€ category. Practicality of e-modules from learner responses obtained an average percentage of 82% in the â€œvery practicalâ€ category. The effectiveness test through N-Gain shows an increase in learning outcomes from a pretest score of 43.83 to a posttest of 85.17, with an N-Gain score of 73.54% which is classified as â€œquite effectiveâ€. From the overall results, the EL-based chemistry e-module on reaction rate material is declared valid, practical, and effective enough to be used as teaching material in the chemistry learning process. Keywords: E-Modules, Experiential Learning, Reaction Rate, ADDIE Abstrak: Penelitian ini bertujuan untuk mengembangkan e-modul kimia berbasis model Experiential Learning (EL) pada materi laju reaksi serta menguji validitas, praktikalitas, dan efektivitasnya. Metode yang digunakan adalah model pengembangan ADDIE (Analysis, Design, Development, Implementation, Evaluation). Subjek penelitian adalah 30 peserta didik kelas XI MIPA 2 di SMA Swasta PAB 8 Saentis. Hasil validitas e-modul oleh ahli materi dan media menunjukkan persentase kelayakan isi sebesar 83%, penyajian 84%, aspek EL 80%, kegrafikan 81%, dan bahasa 87%, dengan rata-rata 83% yang termasuk kategori "sangat layak". Praktikalitas e-modul dari respon peserta didik memperoleh persentase rata-rata 82% dengan kategori sangat praktis. Uji efektivitas melalui N-Gain menunjukkan peningkatan hasil belajar dari nilai pretest sebesar 43,83 menjadi posttest 85,17, dengan skor N-Gain sebesar 73,54% yang tergolong cukup efektif. Dari keseluruhan hasil, e-modul kimia berbasis EL pada materi laju reaksi dinyatakan valid, praktis, dan cukup efektif sehingga layak digunakan sebagai bahan ajar dalam proses pembelajaran kimia. Kata kunci: E-Modul, Experiential Learning, Laju Reaksi, ADDIE